TRACE METALS DETERMINATION IN CHICKEN EGGS - Khalid, N.; Rahman, S.; Ahmad, S.; Ali, S. (The Nucleus, 2020)
To evaluate the adequacy for essential metals and to get an estimate of toxic metals variation in poultry farm and domestic chicken eggs, concentrations of those trace metals which are problematic with neutron activation analysis i. g., Cu, Fe, Mn, Zn, Pb and Cd were carried out using atomic absorption spectrophotometry. The samples were digested with HNO3 ï€ HClO4 mixture. Median concentrations of Cu, Fe, Mn and Zn in the yolk of poultry farm eggs were found to be 3.6, 101.2, 1.7 and 42.3 ïg g-1 respectively. As expected the concentrations of these elements were much lower in egg albumen. On the other hand the median concentrations of Pb (0.130 ïg g-1) and Cd (0.049 ïg g-1) were higher in egg albumen as compared to egg yolk. Almost similar pattern was observed from the analytical data of domestic chicken eggs. The results obtained were compared with the reported results from the literature. Using the average concentrations, daily intake values of these elements were calculated for poultry farm eggs and were found to be well below the WHO recommended/permissible values for essential and toxic metals.